The use of expert review in component development for customer satisfaction towards e-hailing - Nur Athirah Nabila Mohd Idros; Hazura Mohamed; Ruzzakiah Jenal (Institute of Advanced Engineering and Science, 2020)
The emergence of e-hailing apps has increased the demand of customers because online transportation service is very convenient in this modern society. As e-hailing provides an online platform for booking a ride, this apps also functions to connect the customer and driver, while at the same time allowing the customers to interact with customer service that company has provided to keep track of the satisfaction. Competition among e-hailing companies has increased since customers nowadays are very influential and knowledgeable in terms of choosing any transportation services that they want. The purpose of this study is to identify customer satisfaction towards e-hailing by embedding value co-creation model. Value co-creation is one of the concepts in Service Science that has been proved to increase customer satisfaction. Value co-creation is focused on company-customer interaction that helps in maintaining a good customer relationship and improve the company’s performance. Expert identification and evaluation procedure are used as a technique to adapt the definition of value co-creation model towards e-hailing. Then, the other factor from previous studies will be proposed as a component to be listed under value co-creation model and reviewed by an expert.